2003
DOI: 10.1093/protein/gzg041
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of post-fusion 6-helix bundle of heptad repeat regions from Newcastle disease virus F protein

Abstract: Fusion of paramyxovirus to the cell involves receptor binding of the HN glycoprotein and a number of conformational changes of F glycoprotein. The F protein is expressed as a homotrimer on the virus surface. In the present model, there are at least three conformations of F protein, i.e. native form, pre-hairpin intermediate and the post-fusion state. In the post-fusion state, the two highly conserved heptad repeat (HR) regions of F protein form a stable 6-helix coiled-coil bundle. However, no crystal structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…Some studies showed that the HN protein associates with the F protein via specific interaction between the heptad repeat regions of both proteins. For Avian parainfluenza virus-1 (APIV-1, NDV), the head region (HNH) might interact with the HR2 region [8] , and HR2 might interact with HR1 [9] . For Avian parainfluenza virus-1 (APIV-1, NDV), the head region (HNH) might interact with the HR2 region [8] , and HR2 might interact with HR1 [9] .…”
Section: Doi: 101360/982005-764mentioning
confidence: 99%
“…Some studies showed that the HN protein associates with the F protein via specific interaction between the heptad repeat regions of both proteins. For Avian parainfluenza virus-1 (APIV-1, NDV), the head region (HNH) might interact with the HR2 region [8] , and HR2 might interact with HR1 [9] . For Avian parainfluenza virus-1 (APIV-1, NDV), the head region (HNH) might interact with the HR2 region [8] , and HR2 might interact with HR1 [9] .…”
Section: Doi: 101360/982005-764mentioning
confidence: 99%
“…In addition, the structure of a substrate-analogue inhibitor complex shows an unexpected mode of inhibitor binding and provides structure basis for rational drug design. , was purified by GST-glutathione affinity chromatography, cleaved with GST-rhinovirus 3C protease (11), and the recombinant SARS-CoV M pro was further purified by using anion-exchange chromatography. The purified and concentrated SARS-CoV M pro (10 mg͞ml) was stored in 10 mM Tris⅐HCl, pH 7.5͞1 mM DTT͞1 mM EDTA.…”
mentioning
confidence: 99%
“…The conserved stalk domain (the HR region) is critical to the role of HN in the promotion of fusion and may be directly involved in its interaction with the F protein HR regions [7] . For Avian parainfluenza virus-1 (APIV-1, NDV), the head region (HNH) might interact with the HR2 region [8] , and HR2 might interact with HR1 [9] . Therefore the relationships among the HNH, HR1 and HR2 are the key questions in the research of the HN-F interaction domains.…”
Section: Doi: 101360/982005-764mentioning
confidence: 99%
“…We chose a BLAST (http://www.ncbi.nlm.nih.gov/ BLAST) analysis program in identifying HNH of APIV-2 HN protein and HR1 and HR2 regions of F protein by comparing them with relative regions of APIV-1 published recently [8,9] . Meanwhile, we chose the LearnCoil-VMF (http://nightingale.lcs.mit.edu) program to identify F protein heptad repeat coiled coils.…”
Section: Gene Constructionmentioning
confidence: 99%